REGULASI DIRI DAN INTENSITAS PENGGUNAAN SMARTPHONE TERHADAP KETERAMPILAN SOSIAL - SYAFRIDA, RINA (Jurnal Pendidikan Usia Dini, 2014)
Abstract: This research background is because 3rd grade students at SDS Jatisampurna Bekasihave low social skill. The students maintain relationship with their same age friends, manystudents dont want to get involve in group activity, but they prefer to do individual activity. Theaims of this research are to find out the influence the intensity of using smartphone toward socialskill, influence of self regulation toward social skill and the influence of self regulation toward theintensity of using smartphone. Variables of this research are the intensity of using smarphone(X1), self regulation (X2) and social skill (X3). This research was using quantitative approach,survey method, and path analysis technique. This research had been done to 3rd grade students atSDS Jatisampurna Bekasi with total sampling 50 students. The result of this reseach showed thatthe intensity of using smartphone is positively influencing directly toward social skill. Selfregulation is positively influencing directly toward social skill. Self regulation is positivelyinfluencing directly toward the intensity of using smartphone. Key word: SelfRegulation, Intensity ofUsing Smartphone, Social Skill Abstrak: Penelitian dilakukan karena rendahnya keterampilan social anak kelas III pada SDS diKelurahan Jatisampurna Bekasi. Anak-anak tidak mau terlibat dalam kegiatan kelompok temansebaya dan lebih suka melakukan kegiatan yang bersifat individual. Penelitian ini bertujuan untukmengetahui pengaruh intensitas penggunaan smartphone terhadap keterampilan sosial, pengaruhregulasi diri terhadap keterampilan sosial dan pengaruh regulasi diri terhadap intensitaspenggunaan smartphone. Variable penelitian yaitu: Intensitas penggunaan smartphone (X1),Regulasi diri (X2) dan keterampilan sosial (X3). Penelitian ini menggunakan pendekatankuantitatif, metode survey dan teknik analisis jalur. Sampel populasi adalah kelas III SDS,Kelurahan Jatisampurna Bekasi sebanyak 50 anak. Hasil penelitian menunjukkan intensitaspenggunaan smartphone berpengaruh langsung positif terhadap keteram-pilan sosial. Regulasi diriberpengaruh langsung positif keterampilan sosial. Regulasi diri berpengaruh langsung positifterhadap intensitas penggunaan smartphone. Kata Kunci: Regulasi diri, Smartphone, Keterampilan Sosial